Impact of rehabilitation programs on dependency and functional performance of patients with major lower limb amputations: A retrospective chart review in western Saudi Arabia - AlSofyani, Mohammad A. (Saudi Med J, 2016)
OBJECTIVES: To determine pattern and impact of physical rehabilitation on dependency and functional performance of patients. METHODS: This retrospective chart review was carried out between July and August 2012 at King Abdulaziz Medical City, Jeddah, Saudi Arabia. Data were collected using demographic, clinical, and dependency assessment checklists. RESULTS: Patients who underwent major lower limb amputations between January 2007 and April 2012 (n=121) were included in the study. There were 84 (69.4%) male and 37 (30.6%) female patients with a mean ± standard deviation of 63.3±17.4 years old. Diabetes mellitus was the most frequent cause in 63.6% of patients. Only one-third of the amputees (32.2%) have records of completion of their rehabilitation programs, although 20.7% of them completed the <50% of the scheduled rehabilitation sessions, 17.2% attended between 50% and 80%, and the remaining 62.1% attended more than 80% of the scheduled sessions. Muscle power scores in each side of the upper and lower limbs were significantly better following rehabilitation (p<0.0001). Basic functions of mobility and transfer have also significantly improved (p<0.05). CONCLUSIONS: Overall dependency and functional performance were significantly better following implementation of the physical rehabilitation programs. A multidisciplinary team approach is mandatory to improve compliance of patients toward the rehabilitation programs.